Recent recruiting trends and their implications for models of enlistment supply - Murray, Michael P., 1946-; United States. Department of Defense. Office of the Secretary of Defense; United States. Army.; National Defense Research Institute (U.S.); Rand Corporation (Santa Monica, CA : RAND, 1999)
The authors estimate an econometric model of high-quality enlistment supply using geographically disaggregated data from two periods, FY83-87 and FY90-93. They find that econometric models based on data from the earlier period do not predict the recruiting difficulties reported by the military in the 1990s. This conforms to a preliminary assessment provided by Asch and Orvis (MR-549-A/OSD, 1994). The authors also find that econometric models estimated with the 1990s data give altered counsel about the effects of at least some policy variables, most notably the number of recruiters.
Figures vii -- Tables ix -- Chapter 2 Variables Influencing Enlistment Supply 7 -- Chapter 3 The Econometric Models 21 -- Chapter 4 Empirical Results 31 -- Chapter 5 Conclusions and Recommendations 51.
"Prepared for the Office of the Secretary of Defense and the U.S. Army."
Includes bibliographical references (pages 81-83).
Print version record.
English.
eBooks on EBSCOhost
Keywords: Soldiers -- Supply and demand -- United States -- Forecasting; TECHNOLOGY & ENGINEERING -- Military Science; HISTORY -- Military -- Other; United States